An Ethnobotanical Study of Medicinal Plants in the Greek Islands of North Aegean Region - Axiotis, Evangelos; Halabalaki, Maria; Skaltsounis, Leandros A. (Frontiers in Pharmacology, 2018)
Greek islands of the North Aegean Region are a group of nine inhabited islands (Lemnos, Agios Efstratios, Lesvos, Chios, Psara, Oinousses, Samos, Ikaria, and Fourni) located in the northern part of the Aegean Sea, close to Asia Minor. Each island of this region can be considered autonomous in terms of culture and biodiversity. With this work we try to evaluate the status of the traditional uses of medicinal plants in this region. Endemic and endangered species such as Sideritis sipylea Boiss., Origanum sipyleum L., Thymus sipyleus Boiss., Pistacia lentiscus L., Verbascum ikaricum Murb., are still used by locals to treat different ailments. Moreover, the use of some species for the treatment of specific diseases has been reported for the first time. We report about 109 wild plants of medicinal importance, from 52 families, listing their uses for therapeutic purposes and galenic preparations provided by local medical doctors and pharmacists. The information we include was derived from literature sources and additionally collected through semi-structured interviews conducted on 200 informants (100 men and 100 women). Additionally, informant consensus factor (FIC) and UV value were calculated for the medicinal plants in the current study in relation with the diseases treated. This research confirms the importance of the medicinal plants and the diffusion of their use in traditional medicine within this region. This ethnopharmacological survey is a fundamental step for the preservation of the local knowledge both for further scientific research and for the protection of endangered and endemic medicinal plants.